1997
DOI: 10.1212/wnl.48.4.878
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of brain metabolites in amyotrophic lateral sclerosis by localized proton magnetic resonance spectroscopy

Abstract: Article abstract-We performed proton magnetic resonance spectroscopy ('H-MRS) in patients with motor neuron disease (MND) to determine the absolute in vivo concentrations in the brain of the metabolites N-acetyl aspartate (NAA), choline (Cho), and creatine (CrPCr). We examined the spectra acquired from a 20 X 20 X 20-mm3 voxel placed in the motor cortex and in the cerebellum from seven patients with clinically probable or definite amyotrophic lateral sclerosis (ALS) according to the El Escorial criteria, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 10 publications
5
45
1
Order By: Relevance
“…Previous studies measuring absolute metabolites in ALS have inconsistently found increased Cho, yet all additionally documented decreased NAA. 14,23,[48][49][50] Compared with absolute quantitation, ratio determination provides a simpler and more reliable method with less experimental error. It would be worthwhile to follow up these findings with a study that incorporates absolute quantitation but with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies measuring absolute metabolites in ALS have inconsistently found increased Cho, yet all additionally documented decreased NAA. 14,23,[48][49][50] Compared with absolute quantitation, ratio determination provides a simpler and more reliable method with less experimental error. It would be worthwhile to follow up these findings with a study that incorporates absolute quantitation but with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal marker NAA has been shown to be associated to reduced neuronal integrity and neurodegeneration in ALS. Compared to healthy individuals, ALS patients show reduced levels of NAA the primary motor cortex (Gredal et al, 1997;Han and Ma, 2010;Nelles et al, 2008;Pioro et al, 1994;Pohl et al, 2001;Sarchielli et al, 2001;Suhy et al, 2002;Wang et al, 2006) and brain stem (Cwik et al, 1998;Pioro et al, 1999). Reduced NAA to total creatine ratio in motor cortex of ALS patients correlates with ALS Functional Rating Scale that depicts ALS progression (Sivák et al, 2010).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…A number of studies have demonstrated a reduction in N-acetylaspartate (NAA), a marker of neuronal loss, in patients with ALS compared to controls expressed as absolute concentrations, 11,12 or as ratios of other metabolites like choline (Cho) and creatine (Cr) 10,[13][14][15][16][17][18][19][20][21][22][23][24] in the primary motor cortex, 13,17,19,23,25,26 centrum semiovale, internal capsule, corticospinal tract, cervical spine, 10,12,23 medulla, 5 and brainstem. Whether similar findings might be evident in people at risk for developing ALS, however, remains an unanswered question.…”
mentioning
confidence: 99%